Analisis Strategi Pemasaran Pada Penjualan Beras Organik Hariku di PT Sembada Inti Pangan Jakarta Pusat - Muhammad As’ad; Adisty Nabila Putri (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study aims to determine the Benefits of Organic Rice for daily needs. Researchers used a qualitative approach so that data collection was carried out through interviews. The specified informants are Directors, Sales, and Mandatory Informants from Business Study Program Academics. The population in this study were Hariku Organic Rice customers in Central Jakarta using sources related to Hariku Organic Rice and the STIAMI Campus Academic Community. From the results of the study, it can be concluded that there are still people who do not understand the Advantages of Organic Rice. The Benefits of Organic Rice for the body are widely known by the public, therefore people have tried to buy and experience the Benefits of Organic Rice. Thus, if Hariku’s Organic Rice improves product quality and product cleanliness, there will be an increase in Sales of Hariku’s Organic Rice in Central Jakarta and also becomes a factor in consumer satisfaction, so this effect can be said to be significant. This happens because there is an influence between quality and price with consumer satisfaction whit Hariku’s Organic Rice in Central Jakarta.